Factors Affecting the Age of Menopause in Padang City in 2023 - Bennovry, Rizky Rivonda; SA, Syahredi; Utama, Bobby Indra (Fakultas Kedokteran Universitas Andalas, 2024)
Menopause is characterized by a consecutive period of amenorrhea lasting 12 months without any underlying causes or surgical interventions. The age at which menopause occurs can be influenced by various factors, including menarche, number of childbirths, body mass index, and the utilization of hormonal contraceptives. This study aims to determine the factors that influence the incidence of menopause in Padang. This study is an analytical research with a cross-sectional study design. The research was conducted in the working areas of all primary public health centers in Padang from Januari 2023 to September 2023. The sample consisted of middle-aged women who visited the working areas of all primary public health centers during the study period. This study is using a questionnaire as the research instrument and employing the simple random sampling technique to obtain a sample size of 124 participants. The data analysis was conducted using the Chi- Square test, and utilize the statistical software SPSS. A significant relationship between variables was defined if the p-value < 0.05. The results of this study revealed that the majority of respondents experienced early menarche (36.3%), had multiparous pregnancies (33.9%), had underweight body mass index (33.1%), used hormonal contraceptives (52.4%), and experienced late menopause (40.3%). The analysis showed a significant relationship (p<0.05) between the age of menarche (p=0.036) and parity (p=0.002) with the occurrence of menopause. However, there was no significant relationship (p>0.05) between body mass index (p=0.141) and history of contraceptive use (p=0.069) with the occurrence of menopause. This study found a significant relationship between the age of menarche and parity with the occurrence of menopause, while there was no significant relationship between body mass index and history of contraceptive use with the occurrence of menopause among middle-aged women visiting the primary public health center areas in Padang.